Annual and regional variations of aflatoxin B1 levels seen in grains and feed coming from Croatian dairy farms over a 5-year period. (January 2015) - Pleadin, Jelka; Vulić, Ana; Perši, Nina; Škrivanko, Mario; Capek, Brankica; Cvetnić, Željko
Abstract: The aim of the study was to investigate annual and regional differences in the level of aflatoxin B1 (AFB1 ) in grains and dairy cattle feed. Maize ( n = 972), wheat ( n = 201), barley ( n = 147), oat ( n = 136), grain mixtures ( n = 168), and dairy cattle feed ( n = 325) were sampled from 2009 to 2013 on different farms and in different farm factories situated in four Croatian regions. The samples were analysed for AFB1 using the validated ELISA immunoassay. AFB1 was determined in 16.4% of all investigated samples, among which maize was proven to be the most contaminated, with 21.7% of the samples recovered during 2013 harbouring AFB1 in concentrations over the permissible ones. Levels higher than permitted were observed in 17.9% and 12.3% of grain mixtures and dairy cattle feed, respectively, whereas concentrations of AFB1 determined in other crops throughout the investigated period met the stipulated requirements. The results revealed the AFB1 occurrence to be significantly ( p < 0.05) dependent on the cultivation region, with the highest levels generally found in maize harvested in 2013 and consequently in grain mixtures and cattle feed that can most likely be associated with climatic conditions as the most critical factor for mould formation, and thus also AFB1 production. Highlights: Aflatoxin B1 in grains and feed from dairy farms over a 5-year period was determined. ELISA method was implemented. Contamination levels were dependent on the cultivation region and the year of sampling. The highest levels were generally found in maize. Elevated levels were consequently determined in grain mixtures and feed.